Complaining Behavior Intentions dan beberapa Antesendennya: Peran Gender sebagai Variabel Moderasi - Astarini, Dyah; Pratomo, Luki Adiati (Journal of Management and Business Review, 2021)
This research aims to analyze the factors that affect the complaining behavior intentions that are moderated by gender.Â  The data collection method is done by distribution the questionnaire, directly and online and finally used 225 respondents. Â Hypothesis testing is using SEM. The results of the study were found that the factors affecting complaining behavior were attitudes towards complaining, the level of dissatisfaction, and the importance of the situation. Furthermore, these studies have shown that gender moderates the relationships between attitude towards complaining, level of dissatisfaction, and importance of the situation against complaining behavior intention. For further study, it is advised to research other services industries such as hotels, airline, or banking and add perceived justice variabels